CONSEQUENCES OF FISCAL DEFICIT AND PUBLIC DEBT IN FINANCING THE PUBLIC SECTOR - Tešić, Aleksandra; Ilić, Dragan; Đelić, Anastazija Tanja (Economics of Agriculture, 2014)
The aim of this paper is to highlight the important issues of the budget deficit and public debt and their impact on economic growth. This paper considers the twin deficit hypothesis, which argues that there is a strong correlation between the current account deficit for an economy and government budget deficits. In the last ten years, Serbia is faced with a situation of simultaneous fiscal deficit and current account deficit. However, the growth of gross domestic product and the maturity of the debt obligation indicate that the debt burden increases, the weak development of the economy and the debt, and the power of the state and threatened to open debt crisis, the emergence of foreign insolvency. To explore the effects of budget deficits and public debt in macroeconomic relations and aggregates applied the methods of descriptive statistics, and used the official data of the relevant national and international institutions. The main results of the analysis indicate a crisis of public finances, which are accumulated for many years, with a growing budget deficit and the dominant external financing of the budget deficit.